2007
DOI: 10.1111/j.1439-0531.2006.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Glutathione on the Quality of Chilled Bull Semen

Abstract: Glutathione (GSH) at concentrations of 0.0 (control), 0.5, 1.0, 2.0 and 3.0 mM was added to chilled bull semen to determine its effects on the keeping quality of semen used for artificial insemination (AI). The semen was preserved with egg yolk citrate extender. All samples were stored at 4-8 degrees C for 5 days. Sperm motility and proportion of abnormal acrosome were assessed daily. Sperm motility was significantly (p < 0.01) higher in the semen treated with 0.5 mM glutathione than in untreated semen on each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
5
28
0
3
Order By: Relevance
“…The present finding has correlated with the findings of Sagdeo et al (1990) in 75 percent JY, 62.5 percent JY bulls. Higher rating was recorded by Sagdeo et al (1990) in Pure JY bulls, Raina and Dhami, (2004) in Gir bulls and Munsi et al(2007) in HF crossbred bull, where as, lower values than the present investigation were also reported by Sagdeo et al (1990) in 50 percent JY, 75 percent HF and 62.50 percent HF crossbred bulls. In the present investigation, the average rating of mass motility was more than two; hence the extension of semen was tenable.…”
Section: Mass Activitysupporting
confidence: 48%
See 3 more Smart Citations
“…The present finding has correlated with the findings of Sagdeo et al (1990) in 75 percent JY, 62.5 percent JY bulls. Higher rating was recorded by Sagdeo et al (1990) in Pure JY bulls, Raina and Dhami, (2004) in Gir bulls and Munsi et al(2007) in HF crossbred bull, where as, lower values than the present investigation were also reported by Sagdeo et al (1990) in 50 percent JY, 75 percent HF and 62.50 percent HF crossbred bulls. In the present investigation, the average rating of mass motility was more than two; hence the extension of semen was tenable.…”
Section: Mass Activitysupporting
confidence: 48%
“…The present observation of higher motility in glutathione added semen is comparable to the findings of Jain and Arora (1988) and . However slightly lower value has also been reported by Munsi et al (2007) and Zekariya Nur et al (2005), who reported significantly higher motility percent in glutathione added semen in crossbred bulls. It has been observed that a spermatozoon in liquid medium is propelled forward by flagellar beating initiated from distal centriole through electron transport.…”
Section: Post Thaw Seminal Characterstics Motilitymentioning
confidence: 59%
See 2 more Smart Citations
“…Portanto, animais com deficiência de selênio podem ter suprimida a capacidade de defesa contra doenças infecciosas, que poderiam prejudicar a sobrevivência do embrião (Ashworth 1995). Munsi et al (2007) verificaram melhora na mortalidade espermática progressiva e redução das anormalidades espermáticas de animais tratados com glutationa peroxidase, comparados aos não tratados. O selênio é considerado um antioxidante, tendo como função o co-fator da glutationa peroxidase, enzima responsável pelo sistema de regulação extra e intracelular da hidroperoxidase (Luberda 2005).…”
Section: Importância Do Selênio De Pequenos Ruminantesunclassified